Pengaruh Metode Cooperative Script dalam Meningkatkan Hafalan Kosakata Bahasa Arab Kelas VII MTs Al-Jauhar - Sugiat; Setiawan, Ahmad Hadi; Susanto, Asep Bambang (Al Mitsali : Jurnal Penelitian dan Pendidikan Bahasa Arab, 2024)
The purpose of this research is to find out whether there is an effect of the cooperative script method on increasing students' Arabic vocabulary memorization in class VII Arabic subject. The questions in this study include "Is there any effect of applying the cooperative script method to increasing students' Arabic vocabulary memorization at MTs Al Jauhar Bandar Lampung?". This research is quantitative research using pre-experimental design method. The subjects in this study were students of MTs Al Jauhar Bandar Lampung. Based on the research that has been done, the results of the research for the t test obtained a significance value of 0.000 <0.05, then H0 was rejected and H1 was accepted, thus it can be concluded that there is a positive influence and results between the cooperative script method and increasing the memorization of Arabic vocabulary in the eyes class VII Arabic lessons at MTs Al Jauhar Sukabumi Bandar Lampung.